Sufi Ethics and Religious Moderation through a Revisit of Miftāḥ al-Ṣudūr for Contemporary Social Harmony - Teten, Teten Jalaludin Hayat; Anshori, Ma’sum; Abas, Abdul; Arsyada, Azma Zuhayda (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
Religious moderation has emerged as a crucial framework for addressing contemporary challenges such as radicalism, intolerance and social polarization in pluralistic societies. This study examines the concept of religious moderation through the lens of Shaykh Ahmad Shohibulwafa Tajul Arifin’s teachings in Miftāḥ al-Ṣudūr. Employing a library-based methodology, the research identifies key Sufi principles—tazkiyyah al-nafs (self-purification), mujāhadah al-nafs (struggle against base desires), and maḥabbah (compassionate love)—as core elements for fostering personal spiritual growth and collective harmony. These values are shown to align with the four indicators of religious moderation as outlined by Indonesia’s Ministry of Religious Affairs: national commitment, nonviolence, tolerance, and respect for local culture. The study highlights how practices such as dhikr (remembrance of God) and tawajjuh (spiritual meditation) not only cultivate inner awareness and emotional regulation but also contribute to building inclusive and peaceful communities. While the research focuses on textual analysis, it underscores the potential of Sufi-based approaches to counteract societal fragmentation by emphasizing ethical behavior and inward transformation. Although limited to textual interpretation, the study calls for further research incorporating fieldwork and interdisciplinary perspectives to assess the real-world application of Miftāḥ al-Ṣudūr’s teachings. Overall, the findings affirm the continued relevance of Sufism in shaping resilient, harmonious societies and offer a constructive paradigm for integrating spirituality with social cohesion in the modern era.